To Assess the Knowledge, Attitude, And Practices of Barbers Regarding HIV and HCV Transmission in the Peshawar Region - Habibullah, Ihtisham Khan, Nazish Babar, Khalida Kousar, Ghayas Uddin, Zahid Ullah Khan, (Pakistan Journal of Medical & Health Sciences, 2022)
Introduction/Objective: The primary goal of this study was to assess barbers' knowledge and practices regarding the spread of HIV and HCV infections. Material and Methods: A cross-sectional survey about the knowledge, attitude, and practices of barbers regarding HIV and HCV was conducted in different union councils of Peshawar by selecting 70 hairdresser shops. The barbers were asked to fill out a questionnaire, which was comprised of questions related to their socio-demographic features, knowledge about HIV and HCV, and practices they exercise while providing their services. Results: Most of the respondents were of the age group of 31-45 years (58.6%). 57% were workers while 42.9% were owners of shops. All the respondents were aware of HIV and HCV infections along with their sources and modes of transmission. The source of awareness was friends circle in the majority (45.7%) cases. 60% of the respondents knew about the organ/system targeted by these viruses while only 50% were aware of the progression and outcome of the disease. 70% of participants were aware of the measures to prevent the transmission of these infections. Spiritual personnel was revealed to be the best healers (47%) followed by medical doctors (30%). Only 20% of respondents accepted the use of gloves, aprons, and washing hands while all of the barbers revealed the use of new shaving blades and cleansing of razors and scissors by Dettol for every client. Conclusion: The majority of the barbers had adequate knowledge about HCV and HIV infections and their transmission but compliance with preventive measures was not strictly followed. Keywords: HCV, HIV, Barbers, Knowledge, Attitudes, Practices.